A novel Zr-Y modified silicide coating on Nb-Si based alloys as protection against oxidation and hot corrosion. (December 2020) - He, Jiahua; Guo, Xiping; Qiao, Yanqiang; Luo, Fa
Highlights: A novel Zr-Y modified silicide coating was successfully prepared by two-step process. The coating possesses an excellent oxidation resistance, its mass gain is 1.6 mg/cm 2 . Zr can improve the formation of glass-like scale and good scale/coating interface. The coating has a better hot corrosion resistance than bare alloy and Si-Y coating. Abstract: To protect Nb-Si based alloys from oxidation and hot corrosion attacks at high temperatures, a novel Zr-Y modified silicide coating is fabricated by combining magnetron sputtering and pack cementation. It has been shown that the coating exerts a superior oxidation resistance (mass gain of 1.6 mg/cm 2 ) than Si-Y coating (mass gain of 4.2 mg/cm 2 ), which is attributed to forming a thin, compact and continuous SiO2 scale and favorable scale/coating interface. Due to possessing much better scale adherence and reduced formation rate of scale, the coating possesses a better hot corrosion resistance than substrate alloy and Si-Y coating.